Responsibility of Notaries and Legal Protection for Defective Legal Document - Nur Risca Tri Indarwati (Authentica, 2023)
The practice of legal defects in the Denpasar District Court Decision Number 172/Pdt.G/2015/PN.Dps, began when the Defendants invited the Plaintiff to sign the Deed of Lease and receive payment for the Lease Agreement. When signing the Deed of Lease, the representative of Defendant I in signing the Deed of Lease did not have the authority, but the Plaintiff was still asked to sign the Deed of Lease and the Plaintiff was not given the completeness of the documents that should have been. The research method used is normative juridical by analyzing Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Office of Notary. The research results in this study are that if the deed made by the Notary concerned is not in accordance with the provisions for making notarial deeds in the Notary Position Law, then the Notary concerned can be held liable to pay compensation and the legal protection is not implemented correctly. Because in the decision the court did not punish the Notary concerned to make the deed of lease to pay compensation to the plaintiff as it should.Keywords: Responsibility of the Notary, Legal Protection, Legal Defects.